'Teaching Young Consumers' – food safety in home and consumer studies from a teacher's perspective. (10th July 2014) - Lange, Marie; Göranzon, Helen; Marklinder, Ingela
Abstract In Swedish compulsory school, the subject home and consumer studies (HCS) is an opportunity to create conscious consumers for the future. In Sweden, it has been estimated that half a million cases of foodborne infections occur each year, which has an impact on public health. The numbers of foodborne infections are affected by actions connected to the four Cs in food safety: cooking, cleaning, chilling and cross‐contamination. As foodborne infections in many cases are suspected to occur in private households, it is of research interest to study food safety teaching in HCS. The aim of this study was to investigate food safety as a part of HCS education and to provide insights regarding self‐reported food safety attitude, knowledge and behaviour among HCS teachers in Swedish compulsory schools. A web‐based questionnaire was distributed online in April 2012. A total of 335 teachers across the country participated, representing about one in five HCS teachers in Sweden. A majority of the responding teachers stated food safety as an important part of HCS education. The study indicates that food safety teaching can be done in different ways depending on factors such as working years, formal HCS education and daily routines in the classroom. The food safety routines relevant to a specific learning situation might determine the didactic choices, and thus some other important issues within the framework of the four Cs i.e. cold food storage, heating, storing leftovers, best before date, cooling and cross‐contamination might be neglected. When it comes to teaching food safety, there is no guarantee that the four Cs in food safety will be covered. Issues connected to cleaning seemed to occur more frequently in HCS teaching rather than the broader aspects of food safety.